2020
DOI: 10.5852/ejt.2020.632
|View full text |Cite
|
Sign up to set email alerts
|

New records of Philopterus (Ischnocera: Philopteridae) from Acrocephalidae and Locustellidae, with description of one new species from Regulidae

Abstract: One species of the louse genus Philopterus Nitzsch, 1818 is redescribed and illustrated: Philopterus acrocephalus Carriker, 1949 ex Acrocephalus luscinius (Quoy & Gaimard, 1830), A. melanopogon (Temminck, 1823), A. scirpaceus (Hermann, 1804), A. schoenobaenus (Linnaeus, 1758), Iduna aedon rufescens Stegmann, 1929, I. rama (Sykes, 1832), Locustella sp. and L. ochotensis (von Middendorff, 1853). Philopterus acrocephalus represents the first species of the Philopterus-complex recorded in the family Locustelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 983 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Within the ischnoceran tree, we recovered 14 genetically distinct lineages, several of which we were able to morphologically identify (Figure 3). This is not particularly surprising as numerous ischnoceran species and host associations are being discovered and described globally (e.g., [58,[82][83][84][85][86][87][88]). However, these new descriptions often come from areas that are traditionally understudied in terms of host and louse diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Within the ischnoceran tree, we recovered 14 genetically distinct lineages, several of which we were able to morphologically identify (Figure 3). This is not particularly surprising as numerous ischnoceran species and host associations are being discovered and described globally (e.g., [58,[82][83][84][85][86][87][88]). However, these new descriptions often come from areas that are traditionally understudied in terms of host and louse diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Straka (1987) recorded 105 species of lice from 81 hosts with a total of 111 host-louse associations from an additional 33 locations. Other partial reports of lice from Slovakia were published by Balát (1952Balát ( , 1981a, Štefan (1977), Straka (1982), Mey (1988), Máca (1991), Lukáš et al (1991Lukáš et al ( , 1992, Krištofík et al (1996), Krištofík (1999Krištofík ( , 2000, Janiga & Kubašková (2000), Janiga & mičková (2004Janiga & mičková ( ), goldová et al (2006, Szczykutowicz et al (2006), Sychra et al (2008Sychra et al ( ), martinů et al (2015, Bush et al (2018), Janiga (2018Janiga ( , 2019 and Najer et al (2020).…”
Section: Introductionmentioning
confidence: 99%
“…Identification of the lice was based on Price [56], Gustafsson and Bush [24], Sychra and Literak [71], Rheinwald [58] and Najer et al [46]. Identification of the louse-flies and fleas was based on Chvala [15] and Rosicky [66].…”
Section: Methodsmentioning
confidence: 99%
“…Philopterus gustafssoni, formerly Philopterus reguli [46], is a parasite of Regulus regulus (Linnaeus, 1758) and Regulus ignicapilla (Temminck, 1820), frequently reported from continental Europe [46]. Recently, Najer et al [46] confirmed that Philopterus lice collected from endemic subspecies of goldcrests -R. r. azoricus from São Miguel and R. r. sanctaemariae from Santa Mariaare conspecific with P. gustafssoni (P. reguli) from the mainland. No subspecies of goldcrest occurs on Graciosa [59].…”
Section: Records Of Licementioning
confidence: 99%